(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
In India, the third leading cause of mortality is a neurological damage known as a stroke, which happens when blood flow to the brain is interrupted. Disabilities in the hands and legs are among the most prevalent effects of stroke on humans. Exercise and rehabilitation are crucial in the healing process after a stroke. While there are a variety of exercises that may help with stroke management, job specific training is a typical recommendation. Proprioceptive Neuromuscular facilitation (PNF) is another prominent approach utilised in Proprioceptive Neuromuscular facilitation (PNF). Evidence for the efficacy of task-specific training in neurological rehabilitation is growing. Stroke patients’ quality of life was the primary outcome of this research, which sought to identify the impact of an ICF model-based exercise programme that was both task- and context-based. Mann Whitney U test, intention to treat analysis, and repeated measures ANOVA with generalised estimating equations using the log link function was used to analyse the data. Patients were surveyed in a more casual setting to assess feasibility. Patients’ reports of pleasure, their level of adherence to the exercise programme, and the absence of adverse events all pointed to the program’s viability. Stroke patients living in the community may have benefited more from an exercise programme that focused on the structure/function, activity, and involvement domains of the ICF than from traditional physiotherapy, according to one research. So, it’s clear that while creating an intervention, it’s important to concentrate on all of the ICF domains. Stroke patients were able to benefit from a fitness programme that was both task and context driven.